A Design Flow for Application-Specific Networks on Chip with Guaranteed Performance to Accelerate SOC Design and Verification - Goossens, Kees; Dielissen, John; Gangwal, Om Prakash; Pestana, Santiago Gonzalez; Radulescu, Andrei; Rijpkema, Edwin (Design, Automation and Test in Europe, 2005)
Systems on chip (SOC) are composed of intellectual property blocks (IP) and interconnect. While mature tooling exists to design the former, tooling for interconnect design is still a research area. In this paper we describe an operational design flow that generates and configures application-specific network on chip (NOC) instances, given application communication requirements. The NOC can be simulated in SystemC and RTL VHDL. An independent performance verification tool verifies analytically that the NOC instance (hardware) and its configuration (software) together meet the application performance requirements. The Æthereal NOC's guaranteed performance is essential to replace time-consuming simulation by fast analytical performance validation. As a result, application-specific NOCs that are guaranteed to meet the application's communication requirements are generated and verified in minutes, reducing the number of design iterations. A realistic MPEG SOC example substantiates our claims.